Shallow-water caridean shrimps from southern Bahia, Brazil, including the first record of Synalpheus ul (Ríos & Duffy, 2007) (Alpheidae) in the southwestern Atlantic Ocean - Almeida, Alexandre O.; Boehs, Guisla; Araújo-Silva, Catarina L.; Bezerra, Luis Ernesto A. (Zootaxa, 2012)
In this contribution, we report 33 species of shallow-water marine and estuarine caridean shrimps from southern Bahia, Brazil. Nine taxa are reported for the first time from Bahia: the alpheids Alpheus cf. paracrinitus Miers, 1881, Alpheus cf. rostratus W. Kim & Abele, 1988, Automate cf. evermanni Rathbun, 1901, Leptalpheus aff. forceps Williams, 1965, Leptalpheus axianassae Dworschak & Coelho, 1999, Salmoneus carvachoi Anker, 2007 [previously reported as Salmoneus cf. ortmanni (Rankin, 1898)] and Synalpheus ul (Ríos & Duffy, 2007) (previously reported as Synalpheus cf. pandionis Coutière, 1909); the hippolytid Thor manningi Chace, 1972; and the processid Ambidexter symmetricus Manning & Chace, 1971. Synalpheus ul is reported for the first time in the South Atlantic Ocean, significantly extending its southern limit in the western Atlantic, and is illustrated herein. The presence of Alpheus bouvieri A. Milne-Edwards, 1878, A. cristulifrons Rathbun, 1900 and A. formosus Gibbes, 1850 in Bahia is confirmed. The southern range limit of the hippolytid Merguia rhizophorae (Rathbun, 1900) is extended from the Mamoã River, Ilhéus (14°35’05.6”S; 39°03’10.5”W) to Barra do Cahy, Prado (17°00’45.0”S; 39°10’21.0”W).